1998
DOI: 10.1093/ps/77.7.1045
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of cardiac structure and function in broiler and Leghorn chickens

Abstract: This study was conducted to validate echocardiography in chickens, and to compare cardiac structure and function between broiler and Leghorn chickens. Diameters of the right and left ventricles, and thicknesses of the left ventricular free wall and the interventricular septum were measured echocardiographically in 5- and 7-wk-old chickens from both lines. Images were obtained from minimally restrained, standing birds using a 7.5 MHz probe placed in a parasternal position. End-systolic and end-diastolic echocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
2
18
1
3
Order By: Relevance
“…The RV epicardial boundary was discernible in 50% of the chickens examined. Similar difficulties were observed for broilers in another study, in which the authors reported a 30% success in obtaining of the RV thickness in these animals (Martinez et al, 1998). Noteworthy, there is the same limitation in echocardiography of the human RV, but in the case of the avian heart, this is the greater problem due to closest limits of the ultrasound window.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The RV epicardial boundary was discernible in 50% of the chickens examined. Similar difficulties were observed for broilers in another study, in which the authors reported a 30% success in obtaining of the RV thickness in these animals (Martinez et al, 1998). Noteworthy, there is the same limitation in echocardiography of the human RV, but in the case of the avian heart, this is the greater problem due to closest limits of the ultrasound window.…”
Section: Discussionsupporting
confidence: 62%
“…more closely resembled echocardiographic diastolic values (3.2 ± 0.9 vs 3.1 ± 0.31 mm). Previously it was shown that in Leghorn chickens there was a correlation between diastolic echocardiographic measurements and post-mortem ones (Martinez et al, 1998). At the end of diastole, the MV is pressed to the free wall, so its visualization was not possible (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies affirm that muscular-skeletal development in fast-growing vs slow-growing birds exceeds the cardiovas-cular development (Martinez-Lemus et al, 1998); under this point of view, CN1 birds showed the highest heart percentage (0.41 to 0.44% carcass weight at 70 and 81 days, respectively).…”
Section: Slaughtering Age In Organic Chickensmentioning
confidence: 83%
“…Therefore, the change in volumes of the relative thorax cavity (TV1 and TV3) from days 1 to 42 was lower in broiler chickens ('/9 to (/7%) compared with the layer ('/92 to 107%) and native ('/85 to 122%) birds (Figure 3b,d). -Lemus et al (1998) reported that, in comparison with Leghorn chickens, fast-growing broiler chickens had relatively smaller postmortem myocardial thicknesses, aortic and left ventricular diameters. Vidyadaran et al (1987) showed that the lungs of the adult domestic fowl are far less well-adapted anatomically for gas exchange compared with the non-galliform species.…”
Section: Resultsmentioning
confidence: 99%